Formation of a system of information and analytical support for marketing analysis at the enterprise - Churlei, Eduard G. (Journal of the Belarusian State University. Economics, 2022)
Information and analytical support for the process of making managerial decisions requires a deep study of marketing components. This is due not only to changing competition and customer preferences, but also to the need to evaluate the elements at each level of the operating environment. The novelty of the proposed approach is determined by the instrumental coverage of all levels of the functioning environment with the identification of significant information flows and the reflection of the spectrum of resulting models, as well as the identification of possible directions for further application of the results obtained.